2007
DOI: 10.1007/s10508-007-9222-z
|View full text |Cite
|
Sign up to set email alerts
|

Masturbation in Urban China

Abstract: This study examined the prevalence and sources of masturbatory practice in a nationally representative sample from China completed in the year 2000, with analysis of sources focused on 2,828 urban respondents aged 20-59. In this subpopulation, 13% (95% CI, 10-18) of women and 35% (CI, 26-44) of men reported any masturbation in the preceding year. Prevalence for people in their 20s was higher, and closer to US and European levels, especially for men. Particularly for women, masturbation not only compensated for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
38
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 35 publications
5
38
0
2
Order By: Relevance
“…As Table 2 demonstrates, age patterns in masturbation track those for oral sex, especially among men. We argue that as with oral sex, masturbation is not a compensation for a lack of partnered sex or for unsatisfying sex-conjectures consistent with previous studies on younger age groups in both the United States (Das 2007) and other countries (Das, Parish, and Laumann 2009;Dekker and Schmidt 2002;Kontula and Haavio-Mannila 1995). Among NSHAP men, 63% of those aged 57-64 (i.e., those most likely to have had partnered sex) report any masturbation in the preceding 12 months, compared with 28% of those aged 75-85 (i.e., the men least likely to have had sex).…”
Section: Sexualitysupporting
confidence: 88%
“…As Table 2 demonstrates, age patterns in masturbation track those for oral sex, especially among men. We argue that as with oral sex, masturbation is not a compensation for a lack of partnered sex or for unsatisfying sex-conjectures consistent with previous studies on younger age groups in both the United States (Das 2007) and other countries (Das, Parish, and Laumann 2009;Dekker and Schmidt 2002;Kontula and Haavio-Mannila 1995). Among NSHAP men, 63% of those aged 57-64 (i.e., those most likely to have had partnered sex) report any masturbation in the preceding 12 months, compared with 28% of those aged 75-85 (i.e., the men least likely to have had sex).…”
Section: Sexualitysupporting
confidence: 88%
“…It is equally difficult to see how masturbation develops sexual interests, when greater masturbation frequency is so often associated with impaired sexual function in men (Brody & Costa, 2009;Das, Parish, & Laumann, 2009;Gerressu, Mercer, Graham, Wellings, & Johnson, 2008;Lau, Wang, Cheng, & Yang, 2005;Nutter & Condron, 1985) and women (Brody & Costa, 2009;Das et al, 2009;Gerressu et al, 2008;Lau, Cheng, Wang, & Yang, 2006;Shaeer, Shaeer, & Shaeer, 2012;Weiss & Brody, 2009). Greater masturbation frequency is also associated with more dissatisfaction with relationships and less love for partners (Brody, 2010;Brody & Costa, 2009).…”
mentioning
confidence: 99%
“…A study of married women found that PVI was related to both marital and sexual satisfaction, cunnilingus was unrelated and masturbating the male partner until orgasm was associated with both poorer marital and sexual satisfaction (Hurlbert & Apt, 1994). In a national probability British subsample (Gerressu et al, 2008) and in a Chinese subsample (Das et al, 2009), female masturbation was associated with a series of sexual difficulties, which was confirmed in a Chinese random sample (Lau et al, 2006) and among Arabic women (Shaeer et al, 2012). Also, as discussed above, women who never had PVI orgasm have more difficulties during childbirth (Baxter, 1974) and, as will be discussed below, PVI frequency was found to be protective against breast cancer, but condom use or coitus interruptus were associated with increased risk (Gjorgov, 1978(Gjorgov, , 1998Le, Bachelot, & Hill, 1989;Vessey, Baron, Doll, McPherson, & Yeates, 1983).…”
Section: Independent Confirmationsmentioning
confidence: 98%
“…Congruent with the view that vaginal orgasm has an adaptive role of reinforcing desire for PVI, vaginal orgasm and PVI frequency are consistently associated with sexual satisfaction, relationship satisfaction, greater sexual desire and less risk of sexual dysfunction (Brody, 2007b;Brody & Weiss, 2011b;Costa & Brody, 2007;Fugl-Meyer, Oberg, Lundberg, Lewin, & Fugl-Meyer, 2006;Nutter & Condron, 1983;Philippsohn & Hartmann, 2009;Tao & Brody, 2011;Weiss & Brody, 2009a). In contrast, other sexual behaviors are frequently uncorrelated or correlated with more sexual difficulties (Brody & Costa, 2009b;Brody & Weiss, 2011a;Costa & Brody, 2007;Das, Parish, & Laumann, 2009;Gerressu, Mercer, Graham, Wellings, & Johnson, 2008;Lau, Cheng, Wang, & Yang, 2006;Nutter & Condron, 1983;Philippsohn & Hartmann, 2009;Shaeer, Shaeer, & Shaeer, 2012;Tao & Brody, 2011;Weiss & Brody, 2009a). Although Prause ignores this literature in her review concluding that orgasm has no primary role in rewarding women's sexual behavior, her own data seemingly conform to the pattern: women who considered the vagina the most important site for orgasm (when compared to women for whom the clitoris was the most important site for orgasm) had more desire for sex with a partner, but not more desire for masturbation.…”
mentioning
confidence: 99%